Indonesia - The Rise of Metropolitan Regions : Towards Inclusive and Sustainable Regional Development - World Bank (Washington, DC, 2017)
In recent years, Indonesia has made great strides in economic growth and development. This growth has been accompanied by rapid urbanization that has transformed Indonesian cities. Urbanization has the potential to boost national economic growth by facilitating the emergence of agglomeration and localization economies. Increasing urbanization presents Indonesia with an opportunity to leverage the transformation taking place to ensure that it is harnessed for economic growth and, more importantly, sustained improvements in the quality of life of its community members. Unfortunately, research shows that over the last four decades, Indonesia has not derived optimal returns on urban development, as can be seen by comparisons with the level of benefit derived by other Asian countries passing through similar processes of urbanization. Urbanization in Indonesia is driving the emergence of metropolitan areas whose boundaries stretch beyond the jurisdiction of administratively defined cities, creating an urgent need for mechanisms that optimize and coordinate development beyond the formal city unit. The purpose of this report on Indonesia's regional and urban development is to provide a comprehensive assessment of the country's spatial patterns of urbanization and economic development and to evaluate the extent to which Indonesia's urbanization has fostered increases in agglomeration economies and economic productivity growth. The study provides the analytical work to evaluate such performance and to identify key issues, constraints and opportunities for promoting faster and more inclusive growth. The overarching goal of the study is to provide a timely and rigorous analysis of regional and urban development in order to foster informed policy discussion at the central, provincial and local government levels.